Implementation of State Theory of Law in The Country Based on Pancasila - Faridy Faridy; Mushafi Miftah (Nurani Hukum, 2022)
This article discusses the concept of the rule of law in the Pancasila State. In the rule of law theory, law has a very high position. It is above all. Indonesia as a state of law, as stipulated in the 1945 Constitution of the Republic of Indonesia Article 1 paragraph (3), has an obligation to carry out its state functions so that it is always based on applicable legal norms. Basing on this legal norm is a form of actualization of the values of Pancasila which are the ideals of national law. In the fifth precept, it is stated that justice is intended for the benefit of all levels of society regardless of social classes, so that law enforcement in Indonesia cannot be selective but must adhere to the principle of equality before the law.